Root cortical aerenchyma improves the drought tolerance of maize (Zea mays L.) - ZHU, JINMING; BROWN, KATHLEEN M; LYNCH, JONATHAN P (Plant, cell and environment, 2010)
Root cortical aerenchyma (RCA) reduces root respiration in maize by converting living cortical tissue to air volume. We hypothesized that RCA increases drought tolerance by reducing root metabolic costs, permitting greater root growth and water acquisition from drying soil. To test this hypothesis, recombinant inbred lines with high and low RCA were observed under water stress in the field and in soil mesocosms in a greenhouse. In the field, lines with high RCA had 30% more shoot biomass at flowering compared with lines with low RCA under water stress. Root length density in deep soil was significantly greater in the high RCA lines compared with the low RCA lines. Mid-day leaf relative water content in the high RCA lines was 10% greater than in the low RCA lines under water stress. The high RCA lines averaged eight times the yield of the low RCA lines under water stress. In mesocosms, high RCA lines had less seminal root respiration, deeper rooting, and greater shoot biomass compared with low RCA lines under water stress. These results support the hypothesis that RCA is beneficial for drought tolerance in maize by reducing the metabolic cost of soil exploration.